2019
DOI: 10.14715/cmb/2019.65.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fentanyl on pancreatic cancer cell proliferation and cancer stem cell differentiation

Abstract: Pancreatic cancer is one of the most aggressive cancer due to the late diagnosis and failure to respond to the treatment despite advances in tumor biology and the development of new cancer therapeutic strategies. It has been reported that these characteristics of pancreatic cancer originate from cancer stem cells within the tumor mass. It has also been reported that Fentanyl is a fast-acting analgesic that binds to the mu-opioid receptors and some other mu-opioid receptors are involved in this cancer process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…For example, fentanyl was also demonstrated to inhibit the progression of human gastric cancer [20]. Celik and Duran provided evidence that fentanyl could reduce pancreatic cancer cell proliferation and cancer stem cell differentiation [21]. Zhang et al [22] reported that fentanyl inhibited cell proliferation and invasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fentanyl was also demonstrated to inhibit the progression of human gastric cancer [20]. Celik and Duran provided evidence that fentanyl could reduce pancreatic cancer cell proliferation and cancer stem cell differentiation [21]. Zhang et al [22] reported that fentanyl inhibited cell proliferation and invasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides cancer bulk cells, a few studies have found that fentanyl might affect cancer stem cells. Fentanyl inhibits tumorigenesis from human breast stem cells by inducing apoptosis and decreases the number of pancreatic cancer stem cells [9,10]. However, fentanyl has also been reported to promote breast cancer cell stemness and epithelial–mesenchymal transition [8].…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl promoted breast cancer cell stemness and epithelial–mesenchymal transition [8]. In contrast, fentanyl decreased the number of pancreatic cancer and cancer stem cells in the PANC‐1 cell population [9]. Other pre‐clinical studies also demonstrate that fentanyl inhibits growth and invasion and induces apoptosis in various type of cancer cells [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that anesthesia may affect apoptosis [ 75 , 76 , 86 , 87 , 139 , 140 , 141 , 142 , 143 ]. Wang et al reported that propofol inhibited migration, induced apoptosis of PC cells, and inhibited cell migration in PC cells in vitro by promoting miR-34a -dependent LOC 285194 and E-cadherin upregulation [ 75 ].…”
Section: Tumor Factors: Emt Hypoxia-inducible Factor-1α (Hif-1α) Matr...mentioning
confidence: 99%
“…Sevoflurane can suppress colon cancer cell proliferation and invasion, provoke apoptosis and autophagy, and regulate EMT, actions that may result from the sevoflurane-induced inhibition of the ERK signaling pathway [ 140 ]. Celik et al showed that fentanyl prescription reduced the numbers of tumor cells and tumor stem cells, diminished the stem cell gene expression of markers, and enhanced apoptosis-related gene expression in PC cells [ 86 ]. However, the fact that opioids increased PC cell death was not entirely due to alterations in apoptotic or necrotic pathways [ 142 ].…”
Section: Tumor Factors: Emt Hypoxia-inducible Factor-1α (Hif-1α) Matr...mentioning
confidence: 99%